2014
DOI: 10.1111/jcpt.12169
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection in immunocompetent wheezy infants: the diagnostic value of CMV PCR in bronchoalveolar lavage fluid

Abstract: Bronchoalveolar lavage fluid CMV PCR was superior to blood CMV PCR in diagnosing lower respiratory tract infections caused by CMV in immunocompetent infants. Ganciclovir therapy may be effective in selected immunocompetent wheezy infants with CMV PCR positivity in BAL fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…This study shows that quantifying CMV in NBBAL specimens is useful in diagnosing CMV pneumonitis in infants and is more predictive than plasma viral load. Other studies have shown similar results in lung transplant recipients [Chemaly et al, ; Westall et al, ], and in wheezy immunocompetent infants [Cinel et al, ], but to our knowledge, respiratory specimen quantification has not previously been evaluated in infants with severe pneumonia admitted to ICU.…”
Section: Discussionsupporting
confidence: 61%
“…This study shows that quantifying CMV in NBBAL specimens is useful in diagnosing CMV pneumonitis in infants and is more predictive than plasma viral load. Other studies have shown similar results in lung transplant recipients [Chemaly et al, ; Westall et al, ], and in wheezy immunocompetent infants [Cinel et al, ], but to our knowledge, respiratory specimen quantification has not previously been evaluated in infants with severe pneumonia admitted to ICU.…”
Section: Discussionsupporting
confidence: 61%
“…The high prevalence of CMV in PBB and bronchiectasis is also a novel finding and further research is necessary to determine the clinical significance. A high prevalence of airway colonization with CMV (51%) among immunocompetent wheezing children with no underlying disease has been described, but inflammatory markers were not assessed in that study. Although CMV and EBV are well known opportunistic pathogens in immunocompromized children, little is known about their role in the airways of healthy children or children suffering from endobronchial bacterial airway infection.…”
Section: Discussionmentioning
confidence: 90%
“…And Peres et al has reported that monitoring the CMV reactivation and preemptive or prophylactic treatment are critical for these patients [25]. The emergence of rapid PCR detection methods has facilitated the accurate, rapid, and quantitative detection of CMV DNA in the patient’s bodily fluids [26]. Furthermore, PCR can be used to detect CMV reactivation, although some researchers have reported that CMV reactivation could simply be an indicator of immunecompromise status and illness severity, and may not require diagnostic procedures and treatment [27].…”
Section: Discussionmentioning
confidence: 99%